โมเดลความสัมพันธ์เชิงสาเหตุระหว่างเหตุการณ์ที่สร้างความยุ่งยากใจบรรยากาศในครอบครัว ความแข็งแกร่งในชีวิต และสุขภาพจิตของนักศึกษาพยาบาล - Nintachan, Patcharin; Orathai, Pisamai; Visudtibhan, Poolsuk Janepanish (Nursing Research and Innovation Journal, 2015)
Abstract: This study aims to validate a causal model displaying relationships among the negative events, family atmosphere, resilience, and mental health of nursing students. The accessible population using in this study consisted of 692 nursing students studying at a selected university in Bangkok. Descriptive statistics were analyzed using SPSS for windows program. The hypothesized model was validated using the LISREL program. Results of data analysis showed that the hypothesized model fitted to the empirical data. All causal variables (the negative events, family atmosphere, and resilience) could collectively explain variance of mental health at 52.00 percentages. When considering the influence of the study variables, the results demonstrated that the negative events had direct effect on resilience and mental health and had indirect effects on mental health through resilience. Family atmosphere had direct effect on resilience and had indirect effects on mental health through resilience. Moreover, resilience had direct effect on mental health. The results from this study indicated that nursing students who had a few negative events and harmony in the family would be highly resilient and would less likely experience mental health problems. Therefore, the strategies for promoting mental health in nursing students should decrease the negative events and promoting harmony in the family as well as resilience. Keywords: Family atmosphere, The negative events, Resilience, Mental health, Nursing students ………………………………………………………………… * This study was supported by The Development Potentials of Thai People Project, Faculty of Medicine Ramathibodi Hospital, Mahidol University ** Corresponding author, Assistant Professor, Ramathibodi School of Nursing , Faculty of Medicine Ramathibodi Hospital, Mahidol University, Email: patcharin.nin@mahidol.ac.th *** Assistant Professor, Ramathibodi School of Nursing , Faculty of Medicine Ramathibodi Hospital, Mahidol University